2020
DOI: 10.3390/mi11070703
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Start-Up Time for Microliter-Scale Microbial Fuel Cells (µMFCs) via the Surface Modification of Gold Electrodes

Abstract: Microbial Fuel Cells (MFCs) are biological fuel cells based on the oxidation of fuels by electrogenic bacteria to generate an electric current in electrochemical cells. There are several methods that can be employed to improve their performance. In this study, the effects of gold surface modification with different thiol molecules were investigated for their implementation as anode electrodes in micro-scale MFCs (µMFCs). Several double-chamber µMFCs with 10.4 µL anode and cathode chambers were fabricated using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…It is demonstrated from the previous studies that the deposition of appropriate coatings on metal or nonmetal materials can effectively reduce the adhesion between interfaces and improve the performance [16,25,26]. However, the tribological properties and durability of the SAMs on a certain metal surface have not been comprehensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…It is demonstrated from the previous studies that the deposition of appropriate coatings on metal or nonmetal materials can effectively reduce the adhesion between interfaces and improve the performance [16,25,26]. However, the tribological properties and durability of the SAMs on a certain metal surface have not been comprehensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports, including by our group, have also used functional thin films to better understand the role that surface charge and specific functional groups play in regulating biofilm colonization at bioanode surfaces [ 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Santoro et al [ 36 ] and Şen-Doğan et al [ 35 ] have investigated the role of surface functionalities using self-assembled monolayers of alkyl/arylthiols on gold anodes and they have found that functional layers with ionizable groups can affect startup times and regulate the composition of the bioanode film. On carbon-based materials, aryldiazonium cation chemistry has been used by several groups to deposit well-defined molecular adlayers aimed at investigating the role of charged acid/base groups [ 30 , 31 , 32 , 34 ] and hydrophilic moieties [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…In total, nine papers are published in this Special Issue, covering biosensors and MEMS-based diagnostics applications [1][2][3][4][5][6][7][8][9]. In particular, Dou et al fabricated a wearable contact lens sensor for non-invasive continuous monitoring of intraocular pressure (IOP) [1].…”
mentioning
confidence: 99%
“…Sardesai and coworkers reported on the design and electrochemical characterization of a spiral electrochemical notification coupled electrode platform for biosensing applications [3]. Microbial fuel cells (MFCs) are biological fuel cells based on the oxidation of fuels by electrogenic bacteria to generate an electric current in electrochemical cells.Şen-Dogan et al proposed a new approach for the enhancement of the start-up time for microliter-scale microbial fuel cells (µMFCs) via the surface modification of gold electrodes [4]. The research findings showed that µMFCs modified with thiol self-assembled monolayers (cysteamine and 11-MUA) resulted in more than a 50% reduction in start-up times due to better bacterial attachment on the anode surfaces [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation